A Nonlinear H∞ Set-point Control Method for Turbofan Engines with Disturbances - Cheng, Dingding; Liu, Lijun; Yu, Zhen (International journal of control, automation, and systems, 2021)
To provide desired control performance for turbofan engines subject to external disturbances, a nonlinear H ∞ set-point control approach is proposed in this paper. The nonlinear H ∞ set-point control expands the scope of controllable operation and limits the impact of disturbances on turbofan engines, which can effectively reduce the frequency of controller switching and improve the stability of the control system. Firstly, a simple polynomial nonlinear state-space model is employed to approximate the nonlinear dynamics of turbofan engines in certain operating conditions. Then, the nonlinear H ∞ set-point controller is designed to ensure the states of turbofan engines robust to exogenous disturbances. Finally, it is proven that the proposed controller guarantees asymptotic stability and robustness. Simulation results show that the proposed method can improve transient responses, disturbance rejection, surge margins, and fuel consumption for the component level engine model JT9D.